TELAAH HIDDEN CURRICULUM PENDIDIKAN ISLAM DALAM AL-QURAN SURAH LUQMAN - Sabriadi HR (Didaktika : Jurnal Kependidikan, 2020)
AbstractThis library research aims to examine the value of Islamic education contained in Al-Qur'an Surah Luqman which has the potential to become a hidden curriculum in the practive of Islamic education, especially in family education. Data was collected by reviewing all relevant documents about Surah Luqman verses 12-19. The collected data then were analyzed with hystorical and philosophical approaches. Exploration of Islamic education value as stated in the Holy Quran Surah Luqman verses 12-19 is a necessity due Luqman'a advice to his son actually bocomes a hidden curriculum in the practice of Islamic education. The educational value contained in Quran Surah Luqman (31) covers three main points; 1) aqidah (faith) education which is described in verses 12-16 as a form o fmonotheism value by enslaing oneself to Allah and not associating Him with any creatures, even if parents invite associates with Allah, 2) moral education as described in verse 17, the command to do prayer, call for kindness and prevent evil and the command to be patient with the tests befall them, 3) the moral education contained in verses 18019 refers to the courtesy in teracting with fellow himans.Keywords: hidden curriculum, Islamic education, Al-Quran Surah Luqman  AbstractThis library research aims to examine the value of Islamic education contained in al-Quran Surah Luqman which has the potential to become a hidden curriculum in the practice of Islamic education, especially in family education. Data was collected by reviewingall relevant documents about Surah Luqman verses 12-19. The collected data then were qualitatively analyzed with hystorical and philosophical approaches.Exploration of Islamic education value as stated in the Holy Quran Surah Luqman verses 12-19 is a necessity due to Luqman's advice to his son actually becomes ahidden curriculum in the practice of Islamic education.The educational value contained in the Quran SurahLuqman (31) covers three main points.; (1) aqidah(faith) education which is described in verses 12-16 as a form of monotheism value by enslaving oneself to Allah and not associating Him with any creatures, even if parents invite associates with Allah, (2) moral education as described in verse 17, the command to do prayer, call for kindness and prevent evil and the command to be patient with the tests that befall them, (3)the moral education contained in verses 18-19 refers to the courtesy in interacting with fellow humans.Keywords: Hidden curriculum, Islamic education, al-Quran Surah Luqman